Non-destructive techniques for grading of mango: a review - Nandi , Chandra Sekhar (Journal of Postharvest Technology, 2022)
Postharvest grading of fruits is vital to maximizing the profit, as it offers a variety of choices to the customers. This paper presents the recent developments and future scopes in non-destructive techniques for grading of agricultural products like fruit, especially mango. The significant technologies that associated with non-destructive techniques are machine vision, electronic nose (e-nose), near-infrared (NIR) spectroscopy, and multispectral and hyperspectral imaging. In this paper, different non-destructive techniques to assess the quality and safety parameters of fruits as applied by the researchers in the recent past have been discussed. These techniques work on different fruit characteristics like colour, aroma, firmness, defects and chemical compositions, etc. The limitations, challenges and future scopes of research of these techniques, along with a suitable comparison, are presented in this paper. It is concluded that hyperspectral imaging is a great and promising technique for estimation of quality and safety of fruits and food products. Moreover, machine vision is the most widespread and versatile technique for maturity and visual quality detection of fruit at high speed and low-cost applications.